Studies on reproduction of the mullet Mugil platanus Günther, 1880 (Actinopterygii, Mugilidae) from the Mar Chiquita coastal lagoon, Argentina: Similarities and differences with related species - González Castro, Mariano (2011)
The aim of the present study is to provide the first results on the reproductive biology of Mugil platanus, from the Mar Chiquita coastal lagoon (Argentina). To address this topic, we employed mainly female gonads, at both microscopic and macroscopic levels. The following stages of oocyte development were observed: (A) oogonias, (B) primary growth oocyte, (C) cortical alveolus stage, (D) yolked oocytes, and (E) atretic follicle. Also five of the seven stages of gonad maturity were macro and microscopically stated. The potential fecundity ranged between 1,002,026 and 2,548,769 yolked oocytes, with a mean of around 1,800,000 oocytes. The length at first maturity (L 50) was 450.6 total length (TL) and 367.7 standard length (SL) for females, 436.3 TL and 354.9 SL for males, showing a late sexual maturity for both sexes. Seasonal changes in gonadosomatic index (GSI) of females were observed. The mean GSI was ≤1 during six months of the year (January, June-October). Two modes in the ovarian maturation were observed, the most important in April-May and a secondary one in November-December. Both modes, correlated with the CPUE values, are indicative of the mullet migration from the coastal lagoon towards the sea for spawning. Differences and similarities have been found between Mugil platanus and other mugilid species (Mugil cephalus, Mugil curema, Liza aurata, Liza abu, Liza argentea, Myxus elongatus, and Valamugil cunnesius), from the reproductive point of view. The length at first maturity obtained for M. platanus is higher than in other mugilid species and when a relationship between maximum length and L 50 is established the percentage corresponding to Mugil platanus is 75%, while the others range between 50 and 61%.